HIV-associated histoplasmosis early mortality and incidence trends: from neglect to priority. - Antoine Adenis; Mathieu Nacher; Matthieu Hanf; Vincent Vantilcke; Rachida Boukhari; Denis Blachet; Magalie Demar; Christine Aznar; Bernard Carme; Pierre Couppie (PLoS Neglected Tropical Diseases, 2014)
Histoplasmosis is an endemic fungal infection in French Guiana. It is the most common AIDS-defining illness and the leading cause of AIDS-related deaths. Diagnosis is difficult, but in the past 2 decades, it has improved in this French overseas territory which offers an interesting model of Amazonian pathogen ecology. The objectives of the present study were to describe the temporal trends of incidence and mortality indicators for HIV-associated histoplasmosis in French Guiana.A retrospective study was conducted to describe early mortality rates observed in persons diagnosed with incident cases of HIV-associated Histoplasma capsulatum var. capsulatum histoplasmosis admitted in one of the three main hospitals in French Guiana between 1992 and 2011. Early mortality was defined by death occurring within 30 days after antifungal treatment initiation. Data were collected on standardized case report forms and analysed using standard statistical methods.There were 124 deaths (45.3%) and 46 early deaths (16.8%) among 274 patients. Three time periods of particular interest were identified: 1992-1997, 1998-2004 and 2005-2011. The two main temporal trends were: the proportion of early deaths among annual incident histoplasmosis cases significantly declined four fold (χ2, p<0.0001) and the number of annual incident histoplasmosis cases increased three fold between 1992-1997 and 1998-2004, and subsequently stabilized.From an occasional exotic diagnosis, AIDS-related histoplasmosis became the top AIDS-defining event in French Guiana. This was accompanied by a spectacular decrease of early mortality related to histoplasmosis, consistent with North American reference center mortality rates. The present example testifies that rapid progress could be at reach if awareness increases and leads to clinical and laboratory capacity building in order to diagnose and treat this curable disease.